Role of Non-Coding RNAs in White and Brown Adipose Tissue Differentiation and Development - Lea Sleiman; Sorina Dinescu (Non-Coding RNA, 2025)
Adipocyte differentiation is a complex process in which pluripotent mesenchymal stem cells (MSCs) differentiate and develop into mature fat cells, also known as adipocytes. This process is controlled by various transcription factors, hormones, and signaling molecules that regulate the development of these cells. Recently, an increasing number of non-coding RNAs (ncRNAs), especially microRNAs (miRNAs), have been established to be involved in the regulation of many biological processes, including adipocyte differentiation, development, metabolism, and energy homeostasis of white and brown adipose tissue. Several in vitro and in vivo studies reported the significant role of ncRNAs in either promoting or inhibiting adipocyte differentiation into white or brown fat cells by targeting specific transcription factors and regulating the expression of key adipogenic genes. Identifying the function of ncRNAs and their subsequent targets contributes to our understanding of how these molecules can be used as potential biomarkers and tools for therapies against obesity, diabetes, and other diseases related to obesity. This could also contribute to advancements in tissue-engineering based treatments. In this review, we intended to present an up-to-date comprehensive literature overview of the role of ncRNAs, including miRNAs, long non-coding RNAs (lncRNAs), and circular RNAs (circRNAs), focusing particularly on miRNAs, in regulating the differentiation and development of cells into white and brown adipose tissue. In addition, we further discuss the potential use of these molecules as biomarkers for the development of novel therapeutic strategies for future personalized treatment options for patients.